Short and sporadic injecting cessation episodes as predictors of incident hepatitis C virus infection: findings from a cohort study of people who inject drugs in Montréal, Canada. (28th May 2019) - Fortier, Emmanuel; Artenie, Andreea Adelina; Zang, Geng; Jutras‐Aswad, Didier; Roy, Élise; Grebely, Jason; Bruneau, Julie
Abstract: Background and Aims: For most people who inject drugs (PWID), drug injecting follows a dynamic process characterized by transitions in and out of injecting. The objective of this investigation was to examine injecting cessation episodes of 1–3‐month duration as predictors of hepatitis C virus (HCV) acquisition. Design: Cohort study. Setting: Montréal, Canada. Participants: A total of 372 HCV‐uninfected (HCV RNA‐negative, HCV antibody‐positive or ‐negative) PWID (mean age = 39.3 years, 82% male, 45% HCV antibody‐positive) enrolled between March 2011 and June 2016. Measurements: At 3‐month intervals, participants completed an interviewer‐administered questionnaire and were tested for HCV particles (HCV RNA). At each visit, participants indicated whether they injected in each of the past 3 months (defined as three consecutive 30‐day periods). Injecting cessation patterns were evaluated on a categorical scale: persistent injecting (no injecting cessation in the past 3 months), sporadic injecting cessation (injecting cessation in 1 of 3 or 2 of 3 months) and short injecting cessation (injecting cessation in 3 of 3 months). Their association with HCV infection risk was examined using Cox regression analyses with time‐dependent covariates, including age, gender, incarceration, opioid agonist treatment and other addiction treatments. Findings: At baseline, 61, 26 and 13% of participants reported persistent injecting, sporadic injecting cessation and short injecting cessation, respectively. HCV incidence was 7.5 per 100 person‐years [95% confidence interval (CI) = 5.9–9.5; 916 person‐years of follow‐up]. In adjusted Cox models, sporadic injecting cessation and short injecting cessation were associated with lower risks of incident HCV infection compared to persistent injecting (adjusted hazard ratios = 0.56, 95% CI = 0.30–1.04 and 0.24, 95% CI = 0.09–0.61), respectively. Conclusion: Short and sporadic injecting cessation episodes were common among a cohort of people who inject drugs in Montréal, Canada. Injecting cessation episodes appear to be protective against hepatitis C virus acquisition, particularly when maintained for at least 3 months.